Yellow Princess gets a pet - Crowne, Alyssa, 1965- (Crowne, Alyssa, 1965- Perfectly princess, 2010)
Abby's parents have finally allowed her to adopt a pet, but when her father brings home a big, slobbery yellow dog named Rex, she has her reservations.